The Impact of Global Trends on Organization and Customer Satisfaction - Chin, Ming Hooi; Kee, Daisy Mui Hung; Kong, Rui Yang; Lee, Jia Ying; Yee, Jia Hui; Bhardwaj, Shelly; Chaudhary, Pratima; Pandey, Rudresh (AIBPM Publisher, 2020)
The study aims to examine the impact of global trends on